Cotton waste‐derived biochar and compost improve early growth and AMF association in cotton. Issue 3 (25th August 2022) - Mowrer, Jake; Dembele, Ginette; Strzelec, Andrea; Thapa, Binita
Abstract: Improving the sustainability of cotton ( Gossypium hirusutum L.) production can be achieved by returning organic matter and nutrients to degraded soils. Amendment with biochar prepared from locally available feedstocks has been suggested as a pathway to sustainability. A greenhouse study collaboratively conducted by Malian and Texas A&M investigators evaluated the effect of biochar prepared from two feedstocks readily available in northwestern Africa: cotton field residue and rice ( Oryza sativa L.) hulls, on cotton plants grown to 6 wk. A composted municipal biosolid was included for comparison with the more carbon (C)‐stable biochars. Four soils of contrasting properties were included in the study. Plant growth response variables were all affected by soil type ( p < .0001). Shoot height was improved by biochars and composts in all soils. Root mass was improved by amendment only in the soil with the greatest clay content. Nitrogen (N) uptake was significantly depressed, and phosphorus (P) uptake was increased under biochar and compost amendment in the most coarsely textured soil. No effect on N and P uptake was observed in the soil with the greatest clay content. Ridge regression analysis showed that arbuscular mycorrhizal fungi (AMF) root colonization was positively related to the P content of the amendments (1.41*Pamend ), negatively related to soil P (–0.49*Psoil ) and positively related to both soil pH (2.15*pH) and clay content (1.130*clay%). Results indicate that degraded soils may be restored through amendment with biochar created from locally available feedstock to improve sustainability of cotton production. Soil properties will determine the degree of benefit. Core Ideas: Biochar and compost from locally available field waste are a low‐cost soil amendment. Biochar amendments improved early shoot growth in cotton in four soils. Arbuscular mycorrhizal fungi colonization of roots was positively related amendment P and soil clay. Locally sourced amendments can improve sustainability of cotton in degraded soils.